2010
DOI: 10.1111/j.1468-2370.2009.00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Stages and Cultural Phases: A Critical Review and a Consolidative Model of Corporate Social Responsibility Development

Abstract: Based on a stakeholder-oriented conceptualization of corporate social responsibility (CSR), this paper offers a multi-dimensional, dynamic perspective which integrates moral, cultural and strategic aspects of the CSR development process, together with its organizational implications. Therefore, the authors link existing stage models of CSR development with stakeholder culture and social responsiveness continuums and provide a consolidative model which highlights a seven-stage development process towards CSR, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
310
0
30

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(347 citation statements)
references
References 88 publications
(146 reference statements)
7
310
0
30
Order By: Relevance
“…Supporting (Maon et al 2010), who provide a framework showing the evolution of CSR culture and implementation, we found that CSR giving involved having a corporate strategy, corporate commitment, the correct people to lead and develop the processes, and 'buy-in' and respect for the process throughout the organization, technology to capture and report information enable automation of support processes such as direct employee donations from wages and gift matching etc. All of this takes corporate resources, the least of which are corporate dollars.…”
Section: Is the Csr Giving Process Costly To Imitate?mentioning
confidence: 99%
See 2 more Smart Citations
“…Supporting (Maon et al 2010), who provide a framework showing the evolution of CSR culture and implementation, we found that CSR giving involved having a corporate strategy, corporate commitment, the correct people to lead and develop the processes, and 'buy-in' and respect for the process throughout the organization, technology to capture and report information enable automation of support processes such as direct employee donations from wages and gift matching etc. All of this takes corporate resources, the least of which are corporate dollars.…”
Section: Is the Csr Giving Process Costly To Imitate?mentioning
confidence: 99%
“…Carroll and Buchholtz 2000;Maon et al 2010). It is the most commonly used theoretical framework for evaluating CSR (McWilliams and Siegel 2001), and has been discussed in that context for many years.…”
Section: Stakeholder Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…At the organizational level, CSR has been found to be driven by a myriad of factors including organizational innovation (Asongu, 2007;Hull and Rothenberg, 2008;Porter and Kramer, 2002), culture (Bansal, 2003;Maon, Lindgreen, and Swaen, 2010;Aguinis and Glavas 2012), 8 size and ownership (Gallo and Christensen, 2011), financial strength (Orlitzky, Schmidt, and Rynes, 2003;Campbell, 2007) (Matten and Moon, 2008:407 -emphasis ours), hence the variation of CSR across countries and institutional contexts (Chapple and Moon, 2005;Campbell, 2007;Kim et al, 2013;Amaeshi and Amao, 2009;Jamali and Neville, 2011) 8 .…”
mentioning
confidence: 99%
“…The second is that Anna Doś these responsibilities apply not only to shareholders but also to a broader group of stakeholders (Freeman, 1984). In their in-depth analysis of CSR definitions, Maon et al (2010) observed that the nature of CSR commitment can differ from a voluntary practice to a moral obligation for the company and that different CSR definitions reflect different kinds of considered stakeholders (internal stakeholders, external stakeholders, or the overall society).…”
Section: Corporate Social Responsibility Challengementioning
confidence: 99%